One-pot three-component synthesis of novel spirooxindoles with potential cytotoxic activity against triple-negative breast cancer MDA-MB-231 cells. (1st January 2018) - Eldehna, Wagdy M.; EL-Naggar, Dina H.; Hamed, Ahmed R.; Ibrahim, Hany S.; Ghabbour, Hazem A.; Abdel-Aziz, Hatem A.
Abstract: Triple-negative breast cancer (TNBC) is a highly aggressive malignancy with limited treatment options due to its heterogeneity and the lack of well-defined molecular targets. In our endeavour towards the development of novel anti-TNBC agents, herein we report a one-pot three-component synthesis of novel spirooxindoles6a–p, and evaluation of their potential anti-proliferative activity towards TNBC MDA-MB-231 cells. Spirooxindoles6a, 6e and6i emerged as the most potent analogues with IC50 = 6.70, 6.40 and 6.70 µM, respectively. Compounds6a and6e induced apoptosis in MDA-MB-231 cells, as evidenced by the up-regulation of the Bax and down-regulation of the Bcl-2, besides boosting caspase-3 levels. Additionally, 6e displayed significant increase in the percent of annexin V-FITC positive apoptotic cells from 1.34 to 44%. Furthermore, spirooxindoles6e and6i displayed good inhibitory activity against EGFR (IC50 = 120 and 150 nM, respectively). Collectively, these data demonstrated that6e might be a potential lead compound for the development of effective anti-TNBC agents.